A COMPREHENSIVE CASE STUDY AND LITERATURE ANALYSIS ON THE EFFICACY OF ANTI-VEGF MEDICATION IN TREATING BRANCH RETINAL VEIN OCCLUSION - V. Draganova; P. Draganov (Trakia Journal of Sciences)
Purpose: The goal of this case study and literature review is to assess whether anti-vascular endothelial growth factor (anti-VEGF) medication is effective in coping with branch retinal vein occlusion (BRVO). We present an in-depth examination of the patient’s medical records, diagnostic accomplishments and therapy results utilizing data from a 61-year-old male patient. Methods: A case report with a brief literature review, which gives readers a better understanding of the current state of BRVO therapeutic choices, using data gathered from the Google Scholar and PubMed databases. Results: A 61-year-old male with blurred vision in the upper half of the visual field in his left eye, BCVA OD: 20/20; OS: 20/70, presented to an outpatient clinic in Stara Zagora, Bulgaria. The symptoms started three weeks ago. The patient reported a history of hypertension and hyperlipidemia. He denied any ocular diseases in his family. After an ophthalmology exam, he was recommended anti-VEGF therapy and antihypertensive and lipid lowering medications intake. Conclusion: Coping with BRVO as ophthalmologists is very important for us, because RVO is one of the most common eye diseases. Intravitreal therapy has revolutionized the treatment of retinal vascular diseases, including BRVO. Although these intravitreal agents are effective, our understanding of their specific indications and long -term roles is still evolving. Furthermore, until the underlying occlusive pathophysiology of RVO, our treatments will be limited to temporizing therapies against a chronic disease.